The conserved protein Seb1 drives transcription termination by binding RNA polymerase II and nascent RNA - Wittmann, S; Renner, M; Watts, B; Adams, O; Huseyin, M; Baejen, C; El Omari, K; Kilchert, C; Heo, D; Kecman, T; Cramer, P; Grimes, J; et al. (Nature Publishing Group, 2017)
AbstractTermination of RNA polymerase II (Pol II) transcription is an important step in the transcription cycle, which involves the dislodgement of polymerase from DNA, leading to release of a functional transcript. Recent studies have identified the key players required for this process and showed that a common feature of these proteins is a conserved domain that interacts with the phosphorylated C-terminus of Pol II (CTD-interacting domain, CID). However, the mechanism by which transcription termination is achieved is not understood. Using genome-wide methods, here we show that the fission yeast CID-protein Seb1 is essential for termination of protein-coding and non-coding genes through interaction with S2-phosphorylated Pol II and nascent RNA. Furthermore, we present the crystal structures of the Seb1 CTD- and RNA-binding modules. Unexpectedly, the latter reveals an intertwined two-domain arrangement of a canonical RRM and second domain. These results provide important insights into the mechanism underlying eukaryotic transcription termination.